IMPROVEMENT OF FIDELITY OF MOVING OBJECTS CLASSIFICATION IN GUARD SIGNALING COMPLEXES WITH SEISMIC SENSORS - Volochiy, Bohdan; Zmysnyi, Mykhailo; Ozirkovskyy, Leonid; Onyshchenko, Volodymyr; Salnyk, Yuriy (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
The effectiveness of guard signaling complexes (GSC), when there is an important validity of the classification of moving objects (MO), is evaluated by the following indexes: probability of GSC task execution; probability of partial fulfillment of the task; probability of user’s “deception”. Accordingly, the performance indicators of the GSC, in turn, depend on the indexes of the functionality of its constituents: probability of fixation of moving object by seismic sensor, probability of correct classification of MO type and probability of receiving radio signal by the system of receiving and displaying information (SRDI). The article describes a discrete-continuous stochastic model of of GSC reaction to moving object crossing control zone, in which three seismic sensors are installed. Majority principle of identifying the type of moving object was used on the receiving part of the complex. A comparative analysis of the effectiveness of guard signaling complexes using one, two and three sensors in control zone are carried out.